(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information on the problems of linguistic and extralinguistic issues of translation. We have "learned" and got used to our language to such an extent that we don’t even notice that it is a miracle. Language is a great discovery that humanity has achieved in the process of its development. Let’s suppose that if an intelligent creature with a means of communication other than language was found in the world, he would have believed that the language is a great and powerful weapon at the disposal of mankind and praised the genius of mankind.